ALM 92. - MCKELVEY, SETH (Michigan Quarterly Review)
The article focuses on Alm 92 , Seth McKelvey's experimental poem generated through the Ten-String Lier , a self-built, unreliable word-substitution program inspired by Psalm 92 and the biblical ten-stringed lyre. Topics include the interplay between theology and technology through linguistic puns and programming, the tension between creative openness and structural constraint in digital composition, and the reimagining of devotional writing through algorithmic art.